Characterization and processing of composite PP/UHMWPE filament for fused deposition modelling application - Ahmed Bala, Abduladim Salem (2017)
In this thesis Polypropylene/Ultra-high Molecular Weight Polyethylene (PP/UHMWPE) biomaterial composite was employed to manufacture implant to reconstruct large skull bone defect using Fused Deposition Modelling (FDM). This effort aimed to reduce the cost and processing time of manufacturing of a product like this and make it available to all. The effects of addition UHMWPE on the mechanical, thermal, rheology and toxicity of PP were investigated. All the blends composition were compounded using melt blending in an internal mixer and then extruded into single filaments characterized according to FDM filament specification. Subsequently, the prepared filament was underfed to FDM to manufacture tensile, flexural, and impact samples. This was done under the default setting of process parameters in order to investigate the mechanical behaviour of the composite. Structural morphology of the fracture surfaces of impact samples were investigated to explore microstructure changes related to UHMWPE content. Furthermore, thermal and rheological characterizations were conducted to explore the degradation temperature and process ability of the composites in order to accomplish successful processing in both filament extrusion and FDM processes. MTT assay was also conducted to investigate the composite toxicity. Full and Fractal Factorial Design were employed to investigate the effect of process parameters on the process response for filament extrusion and FDM processes respectively. The study results proved that the addition of 10% of UHMWPE resulted in 57% improvement in impact strength, 9.6% improvement in thermal stability, and 17.9 % in biocompatibility compared to pure PP. In addition, the impact strength improved once again at an estimation of 40.6% increment due to optimization of FDM setting parameters. As a case study, a skull implant was manufactured for a patent in USMUniversity Hospital with 88.13%-dimensional accuracy. Keywords: Biomaterials melt blending, Polymer extrusion, Fused Deposition Modelling (FDM), Bone reconstruction,